Persepsi Orangtua Peserta Didik Kelas V SDN 1 Aikmel Barat Tentang Pelaksanaan Pembelajaran Daring Selama Masa Pandemi Covid-19 Tahun Ajaran 2020/2021 - Cahyani, Ririn Dwi; Karma, I Nyoman; Saputra, Heri Hadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2021)
This study aims to describe the perceptions of parents of fifth-graders at SDN 1 Aikmel Barat regarding the implementation of online learning during the COVID-19 pandemic. This study uses descriptive qualitative research with the research subject of teachers and parents of class V SDN 1 Aikmel Barat. Data collection techniques are questionnaires and interviews. Data analysis uses the interactive model of Miles and Huberman, namely through data collection, data reduction, data presentation, and drawing conclusions. The results showed that in general the perception of parents was included in the unfavorable category with an overall percentage of 43.42%. In particular, parents' perceptions of online learning are the results of the analysis of response indicators, the percentage is 56.3%. This shows that parents' perceptions are quite good about online classroom media and online learning facilities. The percentage of opinion obtained is 42.06%, this shows that parents' perceptions are not good about online learning materials and parental assistance during online learning. The assessment indicator obtained a score of 31.9%, this shows that parents' perceptions are not good about the implementation of online learning methods.